Ultimate cybersecurity course and CISSP exam prep. (Manning Publications, 2023)
In this course you will learn everything you need to know to take your cyber-security career to the next level. Whether you are already in cyber security and want to prepare for the CISSP exam, or you are working in technology and are curious about what cybersecurity is, this course is for you. The course covers the range of topics that professionals in the field need to know about security and risk management in organizations, including best practices for security in architecture, networking, and physical locations. You'll learn how organizations test and monitor for security, and how they use asset management to discover the data and systems that exist in their organization so they can protect them. And you'll see how security fits into the software development lifecycle We will delve into the importance of security concepts such as confidentiality, integrity, and availability. How to use authentication and authorization to manage user and system access. How organizations prepare for disasters and ready themselves to resume operations. How to use risk management to define your company's approach to security. Supply chain risks. Threat modeling. Security models. Cryptoanalysis. And so much more! We cover a lot of topics here, and when you've finished the course you will have a thorough understanding of how security fits into an organization, and all the areas that need to be secured. Grab a comfy chair and get ready to learn.